Приозерно-балочний ландшафтний район дендропарку “Тростянець”: історія й сучасний стан пейзажних композицій - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
Based on the analysis of literature sources, the estimation of the state of landscape compositions of lakeside-gully area and the methods of architectural constructionof landscapes in the different periods of dendropark Trostyanets evolution was done. The dynamics of the quantity and the occurrence of wood species in the landscape compositions of investigated park area from 1957 to 2007 were represented.